Síntese e caracterização de argilominerais micáceos a partir de rejeito do processamento do caulim - BRITO, Carlos Eduardo Costa (2019)
The Amazon region has large deposits of kaolin, in the process of processing waste isgenerated that without proper disposal can end up becoming an environmental problem. In addition, with constant concern for the environment and advances in the search for new technologies, studies have been conducted in various areas of material science, such as materials reuse and nanotechnology. An example of this is research on special clays and nanoarges. The present work refers to the synthesis and characterization of material synthesized from kaolin tailings, from an industry that performs the processing of kaolin for paper covering installed in the Amazon region. The kaolin tailings were characterized by X-ray diffraction (XRD) and X-ray fluorescence (FRX) characterization, and then calcined at 700 ºC for two hours. To obtain the synthesis gel, in natura and calcined tailings, manganese sulfate and potassium hydroxide were used. The gel was hydrothermally synthesized at 24 and 48 hours and the reaction molar composition remained constant and at varying temperatures (150 and 160 ºC). The synthesis products were characterized by XRD, Scanning Electron Microscopy (SEM), Dispersive Energy Spectroscopy (EDS) and Infrared Spectroscopy (FTIR) assay. The results of the tests show that with the methodology employed in the synthesis reactions, it is possible to produce mycaceous clay minerals from metakaolin from kaolin tailings, as well as from the tailings in their “in natura” form, which represents a cost saving. energy cost of the synthesis process.